SARS‐CoV‐2 infection impacts carbon metabolism and depends on glutamine for replication in Syrian hamster astrocytes. Issue 2 (15th August 2022) - de Oliveira, Lilian Gomes; de Souza Angelo, Yan; Yamamoto, Pedro; Carregari, Victor Corasolla; Crunfli, Fernanda; Reis‐de‐Oliveira, Guilherme; Costa, Lícia; Vendramini, Pedro Henrique; Duque, Érica Almeida; dos Santos, Nilton Barreto; Firmino, Egidi Mayara; Paiva, Isadora Marques; et al.
Abstract: COVID‐19 causes more than million deaths worldwide. Although much is understood about the immunopathogenesis of the lung disease, a lot remains to be known on the neurological impact of COVID‐19. Here, we evaluated immunometabolic changes using astrocytes in vitro and dissected brain areas of SARS‐CoV‐2 infected Syrian hamsters. We show that SARS‐CoV‐2 alters proteins of carbon metabolism, glycolysis, and synaptic transmission, many of which are altered in neurological diseases. Real‐time respirometry evidenced hyperactivation of glycolysis, further confirmed by metabolomics, with intense consumption of glucose, pyruvate, glutamine, and alpha ketoglutarate. Consistent with glutamine reduction, the blockade of glutaminolysis impaired viral replication and inflammatory response in vitro. SARS‐CoV‐2 was detected in vivo in hippocampus, cortex, and olfactory bulb of intranasally infected animals. Our data evidence an imbalance in important metabolic molecules and neurotransmitters in infected astrocytes. We suggest this may correlate with the neurological impairment observed during COVID‐19, as memory loss, confusion, and cognitive impairment. Abstract : Intranasal in vivo infection of Syrian hamster and in vitro infection of astrocytes by SARS‐CoV‐2 induces increased expression of pro‐inflammatory cytokines and interferon‐stimulated genes. Astrocytes infected in vitro also demonstrated dysregulated metabolic pathways with important decrease of intermediates and substrates from tricarboxylic cycle (TCA). Importantly, the blockage of glutaminolysis was critical for the maintenance of viral replication. Protein analysis evidenced that SARS‐CoV‐2 infection both in vitro and in vivo results in enriched pathways associated with neurological diseases and alterations in inflammatory and metabolic pathways which are also found in single‐cell analysis of COVID‐19 patients' brains.